Structural Damage Detection Using a Modified Artificial Bee Colony Algorithm - Xu, H J; Ding, Z H; Lu, Z R; Liu, J K (Computer modeling in engineering & sciences, 2016)
An optimization approach based on Artificial Bee Colony (ABC) algorithm is proposed for structural local damage detection in this study. The objective function for the damage identification problem is established by structural parameters and modal assurance criteria (MAC). The ABC algorithm is presented to solve the certain objective function. Then the Tournament Selection Strategy and chaotic search mechanism is adopted to enhance global search ability of the certain algorithm. A coupled double-beam system is studied as numerical example to illustrate the correctness and efficiency of the propose method. The simulation results show that the modified ABC algorithm can identify the local damage of the structural system efficiently even under measurement noise, which demonstrates the proposed algorithm has a higher damage diagnosis precision.